2018
DOI: 10.1111/omi.12230
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of BrpA in Streptococcus mutans reduces virulence in rat caries model

Abstract: Our recent studies have shown that BrpA in Streptococcus mutans plays a critical role in cell envelope biogenesis, stress responses, and biofilm formation. In this study, a 10-species consortium was used to assess how BrpA deficiency influences the establishment, persistence, and competitiveness of S. mutans during growth in a community under conditions typical of the oral cavity. Results showed that, like the wild-type, the brpA mutant was able to colonize and establish on the surfaces tested. Relative to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…It has been well recognized that biofilm formation helps Salmonella to survive under adverse environment [71]. Importantly, biofilm formation is one of the important virulence determinants of Salmonella and is also associated with resistance against the response of the host immune system [72][73][74]. A previous study showed that biofilm formation was decreased in the Streptococcus mutants cas3 deficiency strain, encoding a type I-C CRISPR-Cas system [75].…”
Section: Discussionmentioning
confidence: 99%
“…It has been well recognized that biofilm formation helps Salmonella to survive under adverse environment [71]. Importantly, biofilm formation is one of the important virulence determinants of Salmonella and is also associated with resistance against the response of the host immune system [72][73][74]. A previous study showed that biofilm formation was decreased in the Streptococcus mutants cas3 deficiency strain, encoding a type I-C CRISPR-Cas system [75].…”
Section: Discussionmentioning
confidence: 99%
“…Also uniquely detected in sfp EMVs was BrpA. BrpA is a surface associated protein with important roles in cell envelope biogenesis, biofilm formation and virulence (Wen et al, 2006(Wen et al, , 2018. Deficiency of this protein in S. mutans impairs biofilm formation (Wen et al, 2006), affects cell division and membrane fatty acid composition thereby reducing acid tolerance, and significantly diminishing the organism's ability to compete within polymicrobial communities and to cause dental caries in a rat model (Wen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To gain insight into the role S. mutans EMVs play in delivering specific protein cargo to the extracellular environment, proteins exclusive to the EMVs or with a fold-change of log2 > 1.5 in EMVs compared to CMs, were tabulated ( Table 1). These results illustrate that S. mutans MV cargo contributes to cell wall development and cell architecture (Wen et al, 2018), bacterial adhesion (Matsumoto-Nakano, 2018), biofilm cell density (Besingi et al, 2017) and matrix development (Bowen and Koo, 2011), and intermolecular competition with other microorganisms (Hamada and Ooshima, 1975). Among the over-represented proteins in the sfp EMVs were BacA (Smu_1340) and BacA2 (Smu_1342) that similar to Sfp are also encoded by genes within the TnSmu2 genomic island.…”
Section: Proteomic Comparison Of S Mutans Emvs and CM Preparationsmentioning
confidence: 91%
“…S. mutans is not known to possess copious cell wall teichoic acids, and key members of the biosynthesis pathway have not yet been identified ( De et al, 2017 ). However, our recent studies have generated evidence that the bacterium also produces phosphate containing polymers besides RGP and whose attachment to the cell wall are catalyzed by BrpA and Psr, two paralogs of the LytR/CpsA/Psr family (LCP) proteins ( De et al, 2017 ; Wen et al, 2018 ). Morphologically, the MecA-deficient mutants resembles the rgpG / brpA / psr triple mutants, which also feature giant cells and multiple asymmetric septa ( De et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%